The long-term mortality impact of combined job strain and family circumstances: A life course analysis of working American mothers - Sabbath, Erika L. (Soc Sci Med, 2015)
BACKGROUND: Work stress and family composition have been separately linked to later-life mortality among working women, but it is not known how combinations of these exposures impact mortality, particularly when exposure is assessed cumulatively over the life course. We tested whether, among US women, lifelong work stress and lifelong family circumstances would jointly predict mortality risk. PROCEDURES: We studied formerly working mothers in the US Health and Retirement Study (HRS) born 1924-1957 (n=7,352). We used sequence analysis to determine five prototypical trajectories of marriage and parenthood in our sample. Using detailed information on occupation and industry of each woman’s longest-held job, we assigned each respondent a score for job control and job demands. We calculated age-standardized mortality rates by combined job demands, job control, and family status, then modeled hazard ratios for death based on family constellation, job control tertiles, and their combination. RESULTS: Married women who had children later in life had the lowest mortality risks (93/1,000). The highest-risk family clusters were characterized by spells of single motherhood (132/1,000). Generally, we observed linear relationships between job control and mortality hazard within each family trajectory. But while mortality risk was high for all long-term single mothers, we did not observe a job control-mortality gradient in this group. The highest-mortality subgroup was previously married women who became single mothers later in life and had low job control (HR 1.91, 95% CI 1.38,2.63). PRACTICAL IMPLICATIONS: Studies of associations between psychosocial work characteristics and health might consider heterogeneity of effects by family circumstances. Worksite interventions simultaneously considering both work and family characteristics may be most effective in reducing health risks.